Effect of pressure on the transformation characteristics of inorganic minerals Na/S in Zhundong coal ash. (October 2021) - Wang, Jianjiang; Wei, Bo; Abudoureheman, Maierhaba; Liu, Kunpeng; Ma, Jinrong; Chen, Lijuan; Mian, Inamullah; Li, Xian; Tan, Houzhang; Li, Guanghui
Abstract: To explore the effect of pressure on the transformation characteristics of inorganic minerals Na/S in Zhundong (ZD) coal ash, the ZD coal ash were calcined by a high-pressure tubular furnace at different pressures (0.1 MPa, 2 MPa and 4 MPa) and temperatures (600–1000 °C every 100 °C intervals). XRF and XRD were used to analyze the mass of each element and inorganic minerals in ash samples. SEM and EDS analyzed the morphological features and elemental distribution. The average crystal size of Na2 Ca(SO4 )2 and Na2 SO4 crystals were calculated, and two crystal structure phases of Na2 SO4 were discussed. The possible mechanism of the inorganic Na/S transformation during 0.1 MPa and 4 MPa were established. The results showed that inorganic substances Na/S mainly existed as Na2 Ca(SO4 )2, Na2 SO4 and CaSO4 in ash samples. With the increase of pressure, the inorganic mineral species including Na/S did not change, and the release ratio of elements Na/S were decreased gradually. Under 4 MPa at 1000 °C, the release ratio of Na/S were 16.80% and 47.23% in raw coal respectively, which were less than 0.1 MPa at 1000 °C (38.68% and 72.37%). High pressure inhibited the release of Na/S in ash, significantly. Na2 SO4 crystals were ordered at room temperature, whereas at high temperature there were disordered O atoms. The pressure promoted the coalescence of Na2 SO4 and CaSO4 into Na2 Ca(SO4 )2, but accelerates the reduction of crystallite size. Highlights: Higher pressure inhibited the release of Na/S inorganic substances significantly. Temperature rising promoted structural phase transition of Na2 SO4 . Higher pressure accelerated the crystallite size of Na2 SO4 and Na2 Ca(SO4 )2 smaller. Higher pressure promoted the coalescence of Na2 SO4 and CaSO4 into Na2 Ca(SO4 )2 .